Ultrastructure and secretion of glandular trichomes in species of subtribe Cajaninae Benth (Leguminosae, Phaseoleae) - De Vargas, Wanderleia [UNESP] (2019)
The subtribe Cajaninae of papilionoid legumes has a pantropical distribution and comprises approximately 490 species. These species have diversified throughout dry environments where there are high temperatures and strong light. The subtribe stands out because all its representatives have vesicular glands. In addition, bulbous-based and capitate trichomes are important secretory structures present in all genera of the Cajaninae. We analyzed the ultrastructure and histochemistry of these glandular trichome types in leaflets of the three species of the subtribe. Using transmission electron microscopy and histochemical analyses, we link the glandular secretions to subcellular structures. We here report for the first time the type of exudate and ultrastructure of the glands of subtribe Cajaninae. Terpenoids and phenolics were confirmed by histochemistry tests, and we observed that the organelles responsible for biosynthesis of oils are the most representative in these glands. Each glandular trichome showed particular ultrastructural features compatible with the compounds produced. We suggest that these glandular trichomes, with their respective exudates, act in defense against herbivory and against possible damage by ultraviolet radiation.